Rural Landscape Characters for Tourism Route Planning - Zakariya, Khalilah; Ibrahim, Putri Haryati; Ibrahim, Illyani; Che Haron, Roziha; Tukiman, Izawati (2020)
Landscape characters of a place are generally understood as visible physical features of a land, which include how natural settings influence ways of living. This research examined the significant landscape characters of the rural corridor that are significant to tourism routes. The case studies were conducted in the Kuala Selangor Route and the East Coast Route, both possessing distinctive landscape characters. It is important that we integrate rural landscape characters into our current and future planning so that they not only contribute to the attractiveness of Malaysia’s tourism corridor but also sustain the country’s unique place characters.